Intergranular stresses in polycrystalline fatigue: diffraction measurement and self-consistent modelling - Korsunsky, A; Jarnes, K; Daymond, MR (2004)
Time of flight neutron diffraction is a highly versatile and truly non-destructive technique that can be used for quantitative analysis of grain level deformation. In the present study neutron diffraction is employed to collect information about the evolution of elastic lattice trains during in-situ fatigue cycling of stainless steel. The measured strains are interpreted through the comparison with a self-consistent polycrystal deformation model. The implications of this analysis for fatigue lifing procedures are discussed. © 2003 Elsevier Ltd. All rights reserved.